Factors associated with the inefficiency of Law 30364, law to prevent, punish and eradicate violence against women and members of the family group, in a peruvian province. - Paco Ale, Alex Efraín (2020)
The research sought to establish the lack of a multidisciplinary team and the lack of collaboration of the person that corresponds to us. The research was not experimental in the transversal design of correlational-causal type, relational level and basic type. It was established that 18.1% of the victims were treated in a timely manner by the legal medical examination and that 17% were subjected to a psychological appraisal in a timely manner. Likewise, 26.4% of the reports are complete. Likewise, it is said that 61.7% of the reports were sent to the JPP Family Court before 24 hours and that 4.5% of the responses to the protective measures before 72 hours. Finally, it was established that the lack of a multidisciplinary team and the lack of collaboration of the victim would be associated with the non-referral of the PNP reports to the Court before 24 hours (p=, 000); not to complete the reports sent from the PNP to the Court (p =, 000); and to the non-issuance of protective measures before 72 hours (p =, 000).